Anemia in Pregnancy: its Renal Complications and Neonatal Outcome: A Community-Level Correlation Study - Sadia Nasir, Aleina Ali Shah, Muhammad Shaukat, Syeda Luba Hussain, Juneda Sarfraz, Seema Ashraf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anemia during pregnancy is a prevalent condition posing public health concern, especially in resource-limited regions where the combination of poor nutrition, late commencement of antenatal visits, and chronic inequities in healthcare access sustain its prevalence. The consequences of anemia on maternal and neonatal outcomes is well documented; however, its possible effects on renal function during pregnancy remain largely overlooked. To examine the correlation between anemia and renal function in pregnant women within a community-based clinical setting, evaluating how hemoglobin levels may relate to markers of renal performance and maternal outcomes. Methods: This cross-sectional study included 71 pregnant women attending the antenatal clinics of a teaching hospital in Peshawar over a one-year period. Participants were referred from both urban neighborhoods and rural areas, including Riorkala, Urmar Miana, Badaber, and Matani, via local Basic Health Units (BHUs) and Rural Health Centers (RHCs). Anemia severity was classified using WHO hemoglobin thresholds. Renal function was evaluated through serum creatinine, blood urea nitrogen (BUN), and estimated glomerular filtration rate (eGFR). Maternal outcomes assessed included birth weight, preterm delivery, and mode of delivery. Results: Most participants had mild (n = 28) or moderate (n = 20) anemia; no cases of severe anemia were found. Mean eGFR was lowest among women with moderate anemia. Although renal impairment (eGFR < 90 mL/min/1.73m²) occurred in both anemic and non-anemic women, no statistically significant correlation was observed between hemoglobin and eGFR (r = 0.06, p = 0.68).Birth weights and preterm delivery rates varied modestly by anemia severity. Anemia was more prevalent in rural participants, who also exhibited lower mean hemoglobin and eGFR values. Conclusion: Anemia in pregnancy remains a prevalent health issue and may be linked with subtle renal changes. While no direct correlation between hemoglobin levels and eGFR was demonstrated, the presence of renal impairment across all anemia categories underscores the importance of routine renal monitoring in antenatal care, especially in underserved rural populations. Keywords: Anemia in pregnancy, renal function, eGFR, maternal outcomes, community health, hemoglobin, antenatal care